Refleksi Implementasi Peraturan Gubernur Lampung Nomor 33 Tahun 2020 yang Menjadi Kontroversi Pemerintah Pusat dari Perspektif Teori George C. Edwards III - Vitriana; Hartuti Purnaweni (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The issue of forest and land fires continues to be suppressed by the Government of Indonesia to achieve the target of 2030 FOLU Net Sink in order to realize the commitment to reduce greenhouse gas (GHG) emissions and sustainable development goal (SDG) No. 13: Climate Action. However, on the other hand, the Lampung Government issued a controversial regulation in 2020, was Lampung Governor Regulation Number 33 of 2020 concerning Management of Sugarcane Harvest and Productivity, which legalizes the practice of burning. With the case study method and literature review with the perspective of George C. Edwards III Theory, the implementation of the regulation is effective from the bureaucratic structure factor, but not the communication, resources, and disposition factors. After a request for formal and material objections, finally on March 19, 2024, by the Supreme Court Decision Number: 1P/HUM/2024, ordered the Governor of Lampung to revoke the regulation.